Comunicación comunitaria y el acceso a la información de los habitantes de la Parroquia La Esmeralda del cantón Montalvo - Sierra Parreño, Melissa Dayanna (2022)
The evident change that this new normality entails limits and allows at the same time many changes, especially in the daily tasks and activities of the individuals who interrelate in a community, community communication is a strategic axis to build and share the voice from the people, give the word to the community, neighborhood, social sector, youth, children, cities, organizations, communities, educational units, universities; teach them to make their own communication and at the same time build a community communication according to the needs, realities and demands of the social sectors, therefore it is essential to measure the changes that it has made to adjust them to the imposed social demands. The present case study refers to community communication and access to information of the inhabitants of the La Esmeralda parish of the Montalvo canton, therefore its objective is aimed at evidencing the communication activities carried out in the community to maintain communication and of the information they receive, for which I use a descriptive methodology of qualitative approach with documentary and field modality, applying the technique of observation and interview directed to the leaders and resident citizens of the La Esmeralda parish, determining that if they have means of communication, which are traditional and that only thanks to the pandemic were forced to investigate virtual communication.